Empowerment of Green Mussel Cultivation for Tambakrejo Residents, Semarang City through the BEM FT UNNES Student Organization Capacity Strengthening Program - Amelia, Dhea; Irsandi, Ridho Fajar; Emyu, Dalnius; Maulana, Sonika (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
The Student Organization Capacity Building Program (PPK- ORMAWA) is a program designed to strengthen the capacity of student organizations in community service in Tambakrejo Village, Semarang City. This program aims to identify important issues that affect food security, financial literacy, waste management, and MSME empowerment, especially in Tambakrejo Village, through the application of six basic literacies. The approach used involves the stages of planning, implementation, and monitoring to solve problems in the village. The planning and preparation process is carried out in coordination with village officials, community leaders, and related partners, with a focus on solving problems through socialization regarding green mussel cultivation with a smart harvest system in Tambakrejo Village. Monitoring and evaluation are carried out after the program is implemented to collect feedback and make improvements. This monitoring and evaluation is an important part of ensuring the success and effectiveness of the program. Through this activity, the team succeeded in strengthening the capacity of the Tambakrejo Village community and providing a positive impact on literacy, the environment, and the local economy.